Integrative Emotional Resilience Model to Improve Blood Pressure Control of Hypertensive Patients: A Phenomenological Study - Sukarmin; Soesanto, Edy; Elly Nurachmah; Sri Yona; Dewi Gayatri; Ratna Aryani (Babali Nursing Research, 2025)
Introduction: Emotional states significantly influence blood pressure among hypertensive patients. This study explores the impact of Islamic spiritual practices and emotional resilience in managing hypertension. Methods: We conducted in-depth interviews with 20 Muslim participants using a qualitative transcendental phenomenological approach. Result: Analysis revealed five primary themes: 1) Suppression of anger through Islamic teachings; 2) Enhanced resilience through religious practices; 3) Improvement in mental relaxation via prayer and dhikr; 4) Physical management to alleviate stress-related symptoms; 5) Socio-cultural activities fostering mental stability. Discussion: The findings suggest that Islamic spiritual practices contribute to emotional resilience by providing coping mechanisms that reduce psychological stress, a known factor in elevated blood pressure. Integrating spiritual, physical, and socio-cultural dimensions creates a holistic approach that supports better hypertension control. This model highlights the importance of culturally and spiritually tailored interventions in chronic disease management. Conclusion: Integrating Islamic spiritual, physical, and socio-cultural approaches enhances hypertension management and patient well-being.